EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI POKOK BANGUN RUANG SISI DATAR DITINJAU DARI KECERDASAN MAJEMUK SISWA SMP NEGERI KELAS VIII SEKOTA MADIUN - Pradana, Lingga Nico; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of the research was to determine the effect of learning models viewed from the student multiply intellegence. The learning models compared were NHT-CTL, NHT and direct instruction. This research Â was a quasi experimental with the factorial design of 3x4. The population of this research was all students class VIII in SMP Negeri at Madiun City. The sampling technique using a stratified cluster random sampling. Samples in this research were 266 students with 91 students as experimental class I, 88 students as experimental class II and 87 students as control class. Data collection methods used documentation, tests and questionnaires method. Hypothesis testing was performed using two-way analysis of variance with unequal cells. Based on the results of hypothesis testing were concluded that: (1) NHT-CTL learning model gave better achievement than NHT learning model and direct instruction, while NHT learning model and direct instruction gave the same achievement, (2) students with type linguistic, logical-mathematical, interpersonal, and spatial had the same achievement, (3) on each type of multiple intelligences, NHT-CTL learning model gave better achievement than NHT learning model and direct instruction, while NHT learning model and direct instruction gave the same achievement, (4) on each models of learning, learning achievement of students with linguistic, logical-mathematical, interpersonal, and spatial had the same achievement.Keywords: cooperative learning NHT, CTL approaches, multiple intelligences, learning achievement